Reliability Analysis Based on Mixture of Lindley Distributions with Artificial Neural Network. Issue 8 (1st June 2022) - Shafiq, Anum; Çolak, Andaç Batur; Swarup, Chetan; Sindhu, Tabassum Naz; Lone, Showkat Ahmad
Abstract: The study of reliability analysis of mixture model is essential in confirming the quality of devices, equipment, and electronic tube flops etc. In recent years, statisticians have developed more interest in mixture model research, notably in the last decade, without taking into account the issue of modeling the metrics of reliability of mixture models using artificial neural networks. In the present study, the influence of pertinent parameters on reliability metrics is studied. The effect of components and mixing parameters for failure function, reversed hazard rate function, mean time to failure, hazard rate function, mean inactivity time, mean residual life, reliability function, Mills Ratio profiles are plotted and discussed. A multi‐layer artificial neural network is developed using the numerical analysis results obtained using four different scenarios. The values extracted from the artificial neural network and the numerical findings of the reliability studies are extensively compared and examined. The deviation rates obtained for the developed artificial neural network model are obtained at values lower than 0.12%. The outcomes demonstrate that neural networks are a powerful and effective mathematical tool that can be used in the reliability analysis of mixing models. Abstract : The findings reveal that the ANN model, which has been developed using data obtained through the use of the suitable statistical model, is an excellent tool for predicting reliability metrics.